Safety assessment of upper water pipeline under the blasting vibration induced by Subway tunnel excavation. (October 2019) - Xia, Yuqing; Jiang, Nan; Zhou, Chuanbo; Luo, Xuedong
Abstract: In order to assess the safety of a buried DN1200 water supply pipeline under blasting vibration induced by subway tunnel excavation, we established a 3D numerical model of the real field engineering based on the Ling-Qing section of Tsingtao Metro Line 3. According to the field blasting monitoring test of ground surface, the reliability of the numerical model and the parameters is proved. Then, the dynamic response of the pipeline in empty state under the blasting vibration is discussed. Meanwhile, the crack strength of reinforced concrete pipe is determined based on the fracture mechanics theory. Based on the analysis, the safety of the empty pipeline under the blasting vibration is assessed. Next, we further assessed the safety of pipeline in the state of full-filled water without pressure and full-filled water with 0.2 MPa pressure (the normal working state). The results indicate that the upper water pipeline in the three states is safe under the blasting vibration induced by subway tunnel excavation with adopted parallel cut blasting method. Highlights: A 3D numerical model is established with the validating of field monitoring. The dynamic responses of pipeline with FSI under three states are calculated. Safety of the pipeline in three states subjected to blasting is evaluated.